Politik Hukum Pengadilan HAM Ad Hoc sebagai Upaya Penyelesaian Pelanggaran HAM Berat Masa Lalu di Indonesia - Pratama, Andhika Yudha (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2022)
This study aimed to analyze gross human rights violations in Indonesia, the implementation of Law Number 26 of 2000 concerning the Ad Hoc Human Rights Court, and the challenges of ad hoc human rights courts in resolving gross human rights violations in Indonesia. This study applied normative and empirical legal research with a case study approach. The researcher collected data from primary and secondary data resources. Data collection techniques were carried out by reviewing, studying, and categorizing. The analysis procedure started with data inspection techniques, data marking, and drawing conclusions. The study results showed that the provision of gross human rights violations in Indonesia was adopted from the Rome Statute. However, the implementation of Law Number 26 of 2000 concerning the Ad Hoc Human Rights Court was still limited to the judicial process of the cases of Timor-Timur and Tanjung Priok. The challenges of ad hoc human rights courts include the less than optimal role of Law Number 26 of 2006, legal aspects of the legislation that were not accompanied by procedural law procedures, law enforcement officers who did not work optimally, as well as political, social, and cultural factors that weaken law enforcement at the national level.